Variações morfológicas em Edessa rufomarginata e revalidação de E. albomarginata e E. marginalis (Heteroptera, Pentatomidae, Edessinae) - SILVA, Eduardo José Ely e (2013)
Based on the types of Edessa rufomarginata (De Geer, 1773) and its synonyms, on morphology of the paramere and coloration, seven patterns are described for E. rufomarginata. Pentatoma furcata Palisot de Beauvois, 1805, Cimex cruentus Fabricius, 1775, Aceratodes flavovirens Stål, 1855 and A. flavomarginatus Stål, 1855 are mantained as junior synonyms of E. rufomarginata. A. albomarginatus Stål, 1855 and A. marginalis Dallas, 1951 are removed from the synonymy of E. rufomarginata and are reinstated in Edessa. Aceratodes discolor Dallas, 1951 is removed from the synonymy of E. rufomarginata and is considered junior synonym of Edessa abdominalis Erichson, 1848.